Differences of Economic Factors on Employment between Industrial Sector in Sidoarjo and Gresik Regencies - Aprilya, Rima Anggun; Sishadiyati, Sishadiyati (PT. Riset Press International, 2024)
The problem of unemployment is increasingly worrying, where unemployment in Sidoarjo and Gresik every year cannot decrease significantly. So the potential level of labor absorption is also getting smaller. Unemployment is a problem that must be overcome by every region. Because high unemployment can lead to decreased productivity, slow economic growth, and increased poverty. This study aims to study, analyze, and compare how the condition of labor absorption in the industrial sector in Sidoarjo and Gresik regencies, as well as to determine the differences in population factors, the number of industrial companies, industrial sector investment, and minimum wages on the absorption of labor in the industrial sector in Sidoarjo and Gresik regencies. The method used in this study is a quantitative approach with secondary data from 2008-2022 with technical analysis of different tests. The result of this study is that the population and number of industrial companies have no difference in the absorption of industrial sector workers between Sidoarjo and Gresik regencies, while there are differences in the investment value of the industrial sector and the minimum wage on the absorption of industrial sector workers between Sidoarjo and Gresik regencies.